The Supernatural and the Miraculous - Clarke, Steve (Sophia, 2007)
Both intention-based and causation-based definitions of the miraculous make reference to the term ‘supernatural’. Philosophers who define the miraculous appear to use this term in a loose way, perhaps meaning the nonnatural, perhaps meaning a subcategory of the nonnatural. Here I examine the aetiology of the term ‘supernatural’. I consider three outstanding issues regarding the meaning of the term and conclude that the supernatural is best understood as a subcategory of the nonnatural. In light of this clarification, I argue that a prominent causation-based definition of the miraculous should be revised so as not refer to the supernatural. I further argue that authors of intention-based definitions of the miraculous need to consider whether or not they should continue to refer to the supernatural, in their definitions of the miraculous, in light of the conclusions discerned here.